2020
DOI: 10.1177/2045125320916657
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as an antidepressant: overview of its mechanisms of action and potential predictive biomarkers

Abstract: Ketamine, a drug introduced in the 1960s as an anesthetic agent and still used for that purpose, has garnered marked interest over the past two decades as an emerging treatment for major depressive disorder. With increasing evidence of its efficacy in treatment-resistant depression and its potential anti-suicidal action, a great deal of investigation has been conducted on elucidating ketamine’s effects on the brain. Of particular interest and therapeutic potential is the ability of ketamine to exert rapid anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 220 publications
(292 reference statements)
1
70
0
1
Order By: Relevance
“…Our study agrees with animal and clinical studies that have reported similar increases in gamma power following acute ketamine administration at therapeutic levels [168][169][170][171][172][173]. Similarly to DBS, subanesthetic doses of ketamine, a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist, also provides a fast antidepressant action [174], being particularly effective in anxious depression [175] and it is also helpful in relieving social anxiety disorder [176]. Cornwell and colleagues found that this rise in gamma power following ketamine administration, measured in cortical magnetoencephalographic recordings, is correlated to antidepressant responses and increased in responders vs. non-responders [177].…”
Section: Effects Of Fg-7142 and Il-dbs On The Spectral Compositionsupporting
confidence: 90%
“…Our study agrees with animal and clinical studies that have reported similar increases in gamma power following acute ketamine administration at therapeutic levels [168][169][170][171][172][173]. Similarly to DBS, subanesthetic doses of ketamine, a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist, also provides a fast antidepressant action [174], being particularly effective in anxious depression [175] and it is also helpful in relieving social anxiety disorder [176]. Cornwell and colleagues found that this rise in gamma power following ketamine administration, measured in cortical magnetoencephalographic recordings, is correlated to antidepressant responses and increased in responders vs. non-responders [177].…”
Section: Effects Of Fg-7142 and Il-dbs On The Spectral Compositionsupporting
confidence: 90%
“…Ketamine, an aryl cyclohexylamine derivative synthesized in 1962, was first introduced into clinical practice as an intravenous (IV) anesthetic agent in 1970 [7]. Ketamine is currently prescribed for the induction and maintenance of general anesthesia via intramuscular (IM) or IV infusion; moreover, over the past two decades, it has emerged as a promising treatment for major depressive disorder (MDD) [8,9]. In addition, increasing evidence now points to its therapeutic efficacy in treatment-resistant depression (TRD), as well as a potential agent for reducing and preventing suicide in depressed patients, as it exerts rapid antidepressant properties as early as several hours after administration.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that a ketamine-mediated antidepressant is sexually dimorphic, but this effect was not detected in ovariectomized female rats [73]. In addition, pharmacokinetic profiling revealed that, as compared with ketamine and its other metabolites (2S,6S;2R,6R), hydroxynorketamines were metabolized in a gender-dependent manner.…”
Section: Metabolitesmentioning
confidence: 99%
“…Opioid (mu, delta, and kappa) receptors are also potential targets ketamine mediated rapid-antidepressant mechanisms [73]. For instance, ketamine attenuated suicidal tendencies through the modulation of opioid receptors.…”
Section: Neurochemical Cascades and Other Mechanismsmentioning
confidence: 99%